Quantification of β-Sitosterol and Puerarin from Pueraria tuberosa DC. by Using High Performance Thin Layer Chromatography - P. MHASKE, HARSHAD; V. VAIDYA, VIKAS; B. KEKARE, MAHARUDRA; A. CHAMPANERKAR, PARIKSHIT; A. PAREKH, SAGAR (Asian Journal of Chemistry, 2010)
Sensitive, simple and accurate high-performance thin-layer chromatographic methods have been established for determination of β-sitosterol and puerarin in root powder of Pueraria tuberosa DC. Methanolic extracts of root powder were used for the experimental work. β-Sitosterol and puerarin were found to be 0.03 and 2.45 %, respectively, in root powder of Pueraria tuberosa DC., by the proposed methods. Separation was performed on aluminium-backed silica gel 60 F254 HPTLC plate for both the standards. Detection and quantification were performed by densitometry at λ = 257 nm and λ = 366 nm for puerarin and β-sitosterol, respectively. Puerarin response was linear over the range 20 to 80 μg mL-1 where as β-sitosterol response was linear over the range 10 to 60 μg mL-1. The validated HPTLC methods can be used for a routine quality control analysis of Pueraria tuberosa DC. and quantitative determination of puerarin and β-sitosterol.